Branching archaeocyaths as ecosystem engineers during the Cambrian radiation. Issue 1 (25th August 2022) - Manzuk, Ryan A.; Maloof, Adam C.; Kaandorp, Jaap A.; Webster, Mark
Abstract: The rapid origination and diversification of major animal body plans during the early Cambrian coincide with the rise of Earth's first animal‐built framework reefs. Given the importance of scleractinian coral reefs as ecological facilitators in modern oceans, we investigate the impact of archaeocyathan (Class Archaeocyatha) reefs as engineered ecosystems during the Cambrian radiation. In this study, we present the first high‐resolution, three‐dimensional (3D) reconstructions of branching archaeocyathide (Order Archaeocyathida) individuals from three localities on the Laurentian paleocontinent. Because branched forms in sponges and corals display phenotypic plasticity that preserve the characteristics of the surrounding growth environment, we compare morphological measurements from our fossil specimens to those of modern corals to infer the surface conditions of Earth's first reefs. These data demonstrate that archaeocyaths could withstand and influence the flow of water, accommodate photosymbionts, and build topographically complex and stable structures much like corals today. We also recognize a stepwise increase in the roughness of reef environments in the lower Cambrian, which would have laid a foundation for more abundant and diverse coevolving fauna.